PENGARUH KADAR AIR TANAH TERHADAP BIOMASSA CACING TANAH Pontoscolex corethrurus - Alfiah Hayati (The East Java Biological Society, 1995)
This research was done in order to study of effect the soil humidity on earthworm Pontoscolex corethrurus biomass. 80 earthworms were placed in plastic pot (12.5 cm in diameter and 10 cm on deep) contained soil media (four individuals in each pot). Four treatment of humidity (45 %, 5 %, 55 % and 60%) with five replication was carried out up to six weeks. At the end of experiment animals were weighting. The difference between pre and post experimental body weigh was calculated, F test was used to test biomass differences among the four conditions of humidity. The result shown that the optimum biomass was in 50% soil humidity in the soil media.